Odpowiedzi

2010-03-04T17:53:08+01:00
-2(2a+3b-6)(3a+3b)-(a+b)²=-2(6a²+6ab+9ab+9b²-18a-18b)-a²+2ab+b²=-12a²-30ab-18b²+36a+36b

(x-y)²-(2x+3y-7)(4x-3x-2)+(2x+2y)(2x+3)=x²-2xy+y²-(8x²-6x-4x+12xy-9xy-6y-28x+21x+14)+4x²+6x+4xy+6y=x²-2xy+y²-8x²+6x+4x-12xy+9xy+6y+28x-21x-14+4x²+6x+4xy+6y=-3x²+23x-xy+y²+12y-14

3(x+4y-5)(x-y)-(3x+2y)²=3(x²-xy+4xy-4y²+5y-5x)-(9x²+12xy+4y²)=3x²-3xy+12xy-12y²+15y-15x-9x²-12xy-4y²=-6x²-16y²-15x+15y-3xy

5(2k+2m-4)(k+2m)-(k-m)²=5(2k²+2km-4k+4km+4m²-8m)-(k²-2km+m²)=10k²+10km-20k+20km+20m²-40m-k²+2km-m²=9k²+32km-20k+19m²

7(z+2w)-(2z-3w-2)+(2z+4w)²= 7z+14w-2z+3w+2+4z²+16zw+16w²=7z+17w-2z+4z²+16zw+16w²+2
2010-03-04T17:57:24+01:00
-2(2a+3b-6)(3a+3b)-(a+b)²=
(-4a-6b+12)(3a+3b)-a²-b²=
-12a²-12ab-18ab-18b+36a+36b-a²-b²=
-13a²-19b²-30ab+36a+36b



3(x+4y-5)(x-y)-(3x+2y)²=
(3x+12y-15)(x-y)-9x²-4y²=
3x²-3xy+12xy-12y²-15x+15y-9x²-4y²=
9x²-16y²+9xy-15x+15y


5(2k+2m-4)(k+2m)-(k-m)²=
(10k+10m-20)(k+2m)-k²+m²=
10k²+20km+10km+20m²-20k-40m-k²+m²=
9k²+21m²+30km-20k-40m

7(z+2w)-(2z-3w-2)+(2z+4w)²=
7z+14w-2z+3w+2+4z²-16w²=
4z²-16w²+5z+17w+2

(x-y)²-(2x+3y-7)(4x-3x-2)+(2x+2y)(2x+3)=
x²-y²-(8x²-6x²-4x+12xy-9xy-6y-28x+21x+17)+4x²+6x+4xy+6y=
x²-y²-(2x²-11x+3xy-6y)+4x²+6x+4xy+6y=
x²-y²-2x²+11x-3xy+6y+4x²+6x+4xy+6y=
3x²+1xy+17x+12y